Knowledge, attitude and practice of Malaysian public university students on viral hepatitis - Mohd Nazri, Nurul Nadia; A. Rahman, Nor Azlina; Mohd Shafri, Mohd Affendi; A.Rahman, Nor Iza; Haque, Mainul (Wolters Kluwer - Medknow, 2019)
Background: Viral hepatitis is a type of liver disease caused by viral infection and is the leading cause of liver cancer and liver cirrhosis. Adequate information, positive attitude and good practice are essential factors to reduce the risk of this disease. This study aimed to evaluate the knowledge, attitude and practice (KAP) regarding viral hepatitis amongst university students in Klang Valley, Malaysia. Methods: A cross-sectional study was conducted on 120 students to represent the population of medical and non-medical science students. A questionnaire was used to collect the data regarding demographic information and KAP of students on viral hepatitis. The Statistical Package for the Social Sciences software was used to analyse the data. Results: The mean total scores of KAP regarding viral hepatitis were significantly higher in medical as compared to non-medical science-based participants with the P < 0.001 for each comparison. A total number of sources of information were also significantly correlated with a higher total score of KAP regarding viral hepatitis (P < 0.001 each). Conclusion: The finding of this study is crucial as it can be the benchmark for assessing the KAP of society regarding viral hepatitis.